VARIASI REPETISI DALAM ANTOLOGI PUISI KARYA PENULIS KALIMANTAN BARAT (Repetition Variation in Poetry Anthologies Written by West Kalimatan Poets) - Damayanti, Wahyu (Salingka, 2017)
The style of the language in the poem is very varied. One of the language styles used in poetry works of West Borneo is repetition. This study aims to describe variations of repetition in anthology of poetry by authors of West Kalimantan. This research uses qualitative descriptive method, with data collection technique; inventory, read-and-record techniques. The results showed that the variation of repetition consisted of repetition of epizeuksis, repetition of tautotes, anaphora repetition, epistrofa reps, the simploke repository, mesodiplosis repetition, epanalepsis repetition, and repetition of anadiplosis. Thus, it can be concluded that the variation of repetition of poetry by authors of West Kalimantan in the Anthology of the Shadows of Tembawang consists of; repetition epizeuksis, repetition tautotes, anaphoric repetition, epistrofa repositions, simploke reps, mesodiplosis reps, epanalepsis repetition, and anadiplosis repetition.